The Diagenetic Alterations of Historic Skeletons from the Crown Mines Cemetery, South Africa - Stacey L. Lander; Margot Hosie; Desiré Brits (Biology, 2023)
Human skeletons associated with early gold mining in Johannesburg, South Africa are investigated. An unmarked cemetery was buried beneath a mine dump which resulted in macroscopically stained and poorly preserved bones. Histological assessments were conducted to understand the postmortem treatment of the remains, determine the extent of bone degradation, and understand how this environment affected the bone’s microstructure. Various diagenetic alterations and the general histological index were assessed using normal and polarized light microscopy of thin anterior midshaft femur sections (n = 50). Degradation was identified in the periosteal and endosteal regions, while the intra-cortical region remained well-preserved. Bacterial bioerosion, microcracks, infiltrations, inclusions, and staining were found throughout the sample. Numerous non-Wedl micro-foci of destruction were observed, filled with exogenous material. The degradation suggested that the remains were buried in neutral soil that was subsequently covered by acidic mine dumps which resulted in a corrosive environment. Although the skeletons were poorly preserved, their histological integrity was more promising, especially the intra-cortical area. This is important for future investigations of archaeological bone, as this area can lead to more accurate descriptions of skeletal assemblages. Targeted sampling of this region could produce promising estimates of age, descriptions of pathology, and biomolecular results, which require further study.